Perkembangan Individu dalam Menghadapi Perkembangan Ilmu Pengetahuan - Wardatuz Zahroh; Maimon Sumo; Maysarotul Sholehah; Umamah (PT. PENERBIT TIGA MUTIARA, 2024)
The development of science is very rapid. Competition is increasingly fierce and people are required to have high intellectual abilities in facing the challenges of the global world. In fact, the progress of a nation will be recognized by the world, one factor is how the majority of people in a country master, develop and utilize science and technology. The purpose of writing this literature review is none other than to explain in detail the development of individuals in facing developments in science, which has so far become a topic of discussion in the world of education. This research uses a descriptive qualitative method, namely research in the form of a literature study which aims to analyze, evaluate, identify, observe, find and determine relevant research topics. The results of data analysis conclude that science and technology are human achievements that must be utilized in understanding and practicing something. In line with this principle, science is actually a process experienced by individuals in their development. The poorer the knowledge, the narrower the insight in understanding something, the narrower a person's thinking about a science. In conclusion, development is a skill in the structure and function of the body or an increase in more complex abilities in a regular and predictable pattern as a result of experience and the maturation process. Development is also very closely related to social, motor, intellectual and emotional abilities. So it becomes very necessary how a learning design is formed to provide freedom to be creative on an ongoing basis in order to optimize and develop students work.